2000
DOI: 10.1007/s004840000062
|View full text |Cite
|
Sign up to set email alerts
|

Phenology in central Europe - differences and trends of spring phenophases in urban and rural areas

Abstract: In order to examine the impacts of both large-scale and small-scale climate changes (urban climate effect) on the development of plants, long-term observations of four spring phenophases from ten central European regions (Hamburg, Berlin, Cologne, Frankfurt, Munich, Prague, Vienna, Zurich, Basle and Chur) were analysed. The objective of this study was to identify and compare the differences in the starting dates of the pre-spring phenophases, the beginning of flowering of the snowdrop (Galanthus nivalis) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(165 citation statements)
references
References 4 publications
13
147
1
4
Order By: Relevance
“…For example, negative trends of the shrub species were more apparent (−0.01 to −3.7 days 10 yr −1 for goldenbell and −0.1 to −3.9 days 10 yr −1 for azalea) than those of the tree species (−0.03 to −0.25 days 10 yr −1 for peach and −0.9 to −2.5 days 10 yr −1 for cherry). Larger shifts in the FFD of early blooming species than of late-blooming species has previously been suggested (Roetzer et al 2000), and this corresponds to the results for shrubs (early FFD) and trees (late FFD) in the present study (see Figure 5). Possibly the early blooming species require less thermal energy accumulation for blooming (which is shown in Section 3.3), and hence are more sensitive to early spring temperature change.…”
Section: Ffd Changesupporting
confidence: 92%
See 2 more Smart Citations
“…For example, negative trends of the shrub species were more apparent (−0.01 to −3.7 days 10 yr −1 for goldenbell and −0.1 to −3.9 days 10 yr −1 for azalea) than those of the tree species (−0.03 to −0.25 days 10 yr −1 for peach and −0.9 to −2.5 days 10 yr −1 for cherry). Larger shifts in the FFD of early blooming species than of late-blooming species has previously been suggested (Roetzer et al 2000), and this corresponds to the results for shrubs (early FFD) and trees (late FFD) in the present study (see Figure 5). Possibly the early blooming species require less thermal energy accumulation for blooming (which is shown in Section 3.3), and hence are more sensitive to early spring temperature change.…”
Section: Ffd Changesupporting
confidence: 92%
“…However, additional environmental factors could affect the vegetation-climate interaction, and plant's response to regional climate change might vary in different parts of the world. As an example, we compared our results with similar findings from Central Europe by Roetzer et al (2000). Figure 10 shows the trends of FFD from the present study and those from Central Europe, during the period of 1951-1995.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In the years 1994-2013, the trend of flowering decreased to 2 days. The results of Roetzer et al (2000) are consistent with our findings, as they showed that 1964 1965 1966 1967 1968 1969 1970 1971 1972 1973 1974 1975 1976 1977 1978 1979 1980 1981 1982 1983 Date flowering linear trend Elevation is a surrogate of a set of meteorological elements (temperature, precipitation), which cause changes in the course of plant phenological phases. With the increasing elevation, flowering in the elevation zones was unevenly delayed by 1 to 15 days in the first period, and by 1-10 days in the second period (Table 1).…”
Section: Resultssupporting
confidence: 91%
“…This is reflected in its highly significant relation to the onset of spring phenological phases (Bednářová et al 2012;Škvareninová 2013). The reaction of the flowering phenophase was also distinct, since in the case of some tree species it has shifted by 14 days earlier over a long-term period (Roetzer et al 2000). In several parts of Europe, it has been observed that an average beginning of the growing season of forest tree species has shifted by 8 days earlier (Chmielewski, Rötzer 2001).…”
mentioning
confidence: 99%